THE PROCESSING OF THE TECHNOLOGY OF CASTING OF THE CYLINDERS BLOCK HEADS OF CAST IRON WITH VERMICULAR SHAPE OF GRAPHITE AT PO “MTZ” - A. N. Krutilin; V. A. Rozum; V. S. Losj; Ju. G. Panarad; A. N. Kuzmich; A. N. Karasj; S. G. Korenjuk (Литьë и металлургия)
The results of adjustment of the technological process of casting of the cylinders block head ingots of cast iron with vermicular shape of graphite are presented.